Mitochondrial TSPO as a target for metabolic syndrome interventions - Kurach, Lukasz (Current Issues in Pharmacy and Medical Sciences, 2025)
The 18 kDa translocator protein (TSPO) is a protein located in the outer mitochondrial membrane that plays a crucial role in mitochondrial transport, maintaining cellular homeostasis, and ensuring normal cell function. TSPO has beneficial effects in regulating various pathophysiological processes, including the inflammatory response, oxidative stress, steroid synthesis and microglial function. The use of TSPO ligands in different experimental settings has led to their translation to clinical trials for treating neurological and psychiatric diseases. Since TSPO drug ligands influence numerous local processes, such as adipokine secretion, glucose metabolism and adipogenesis, TSPO may represent a promising therapeutic target with potential application for metabolic syndrome. From a clinical perspective, targeting mitochondrial metabolism to modulate energy homeostasis is a promising strategy for developing new antidiabetic or anti-obesity drugs. This review aims to summarize current knowledge of TSPO and its potential as a therapeutic target in metabolic syndrome.